2018
DOI: 10.2147/cia.s164174
|View full text |Cite|
|
Sign up to set email alerts
|

Frailty and nutritional status in older people: the Mini Nutritional Assessment as a screening tool for the identification of frail subjects

Abstract: IntroductionFrailty is a condition characterized by reduced resistance to low-level stress events, resulting from the progressive decline of multiple physiological systems observed with aging. Many factors can contribute to the pathogenesis of frailty, and nutritional status appears to play a key role. The objective of the study was to investigate the relationship between nutritional status, evaluated using Mini Nutritional Assessment (MNA), and frailty among older people.Patients and methodsAn observational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 39 publications
(47 reference statements)
2
60
0
10
Order By: Relevance
“…In this connection, systemic inflammation was found not only to reduce albumin synthesis but also to increase its degradation and promote transcapillary leakage [47]. As in the present study, earlier research demonstrated that nutritional status was closely associated with the degree of frailty [48][49][50]. Hence, this association supports the presence of link between pro-inflammatory cytokines and nutritional status.…”
Section: Discussionsupporting
confidence: 86%
“…In this connection, systemic inflammation was found not only to reduce albumin synthesis but also to increase its degradation and promote transcapillary leakage [47]. As in the present study, earlier research demonstrated that nutritional status was closely associated with the degree of frailty [48][49][50]. Hence, this association supports the presence of link between pro-inflammatory cytokines and nutritional status.…”
Section: Discussionsupporting
confidence: 86%
“…Functional decline may be more important and it is associated with the G8 score in elderly patients and the reasons are as follows. The G8 screening tool puts weight on nutritional status and consists of mobility, neuropsychological problems, drugs prescribed, self-assessment health condition, and age, from the Mini-Nutritional Assessment questionnaire [22, 23]. We think that these items may be important factors for reflecting functional decline and predicting chemotherapy tolerance in elderly cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Frailty was more common in the hospitalized patients, while pre-frailty was more prevalent in the outpatient population. [27] We do not know for certain how the prevalence of these syndromes has changed or will change over time, but another study conducted in Swedish elders found the prevalence of geriatric syndromes to be stable over time. [28] Of note, our study found the overlap between frailty and sarcopenia risk to be quite high with 25.1% of older adults screening positive for both frailty and sarcopenia.…”
Section: Plos Onementioning
confidence: 99%